2021
DOI: 10.1002/ese3.902
|View full text |Cite
|
Sign up to set email alerts
|

Cycling performance for storage and purification of lanthanum‐rich mischmetal alloy in the presence of hydrogen sulfide

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Also, when Bio-H2 was used for the MH cartridge, the hydrogen sulfide (H2S) in the fuel caused significant damage on hydrogen capacity of MH. In our previous study, it was found that 100 ppm of H2S reduced the hydrogen capacity of the MH by approximately 20% [7]. Before the cartridge is filled with Bio-H2, impurities must be removed.…”
Section: Introductionmentioning
confidence: 99%
“…Also, when Bio-H2 was used for the MH cartridge, the hydrogen sulfide (H2S) in the fuel caused significant damage on hydrogen capacity of MH. In our previous study, it was found that 100 ppm of H2S reduced the hydrogen capacity of the MH by approximately 20% [7]. Before the cartridge is filled with Bio-H2, impurities must be removed.…”
Section: Introductionmentioning
confidence: 99%